Effect of vitamin D replacement on maternal and neonatal outcomes: a randomised controlled trial in pregnant women with hypovitaminosis D. A protocol - Chakhtoura, M (BMJ Open, 2016)
INTRODUCTION: The vitamin D recommended doses during pregnancy differ between societies. The WHO guidelines do not recommend routine prenatal supplementation, but they underscore the fact that women with the lowest levels may benefit most. The effects of routine supplementation during pregnancy on maternal and neonatal clinical outcomes have not been investigated in the Middle East, where hypovitaminosis D is prevalent. Our hypothesis is that in Middle Eastern pregnant women, a vitamin D dose of 3000 IU/day is required to reach a desirable maternal 25-hydroxyvitamin D [25(OH)D] level, and to positively impact infant bone mineral content (BMC). METHODS AND ANALYSIS: This is a multicentre blinded randomised controlled trial. Pregnant women presenting to the Obstetrics and Gynaecology clinics will be approached. Eligible women will be randomised to daily equivalent doses of cholecalciferol, 600 IU or 3000 IU, from 15 to 18 weeks gestation until delivery. Maternal 25(OH)D and chemistries will be assessed at study entry, during the third trimester and at delivery. Neonatal anthropometric variables and 25(OH)D level will be measured at birth, and bone and fat mass assessment by dual-energy X-ray absorptiometry scan at 1 month. A sample size of 280 pregnant women is needed to demonstrate a statistically significant difference in the proportion of women reaching a 25(OH)D level ≥50 nmol/L at delivery, and a difference in infant BMC of 6 (10)g, for a 90% power and a 2.5% level of significance. The proportions of women achieving a target 25(OH)D level will be compared between the two arms, using χ(2). An independent t test will be used to compare mean infant BMC between the two arms. The primary analysis is an intention-to-treat analysis of unadjusted results. ETHICS AND DISSEMINATION: The protocol has been approved by the Institutional Review Board at the American University of Beirut-Lebanon (IM.GEHF.22). The trial results will be published in peer-reviewed medical journals and presented at scientific conferences. TRIAL REGISTRATION NUMBER: NCT02434380.